Estudio de la toxicidad aguda de un preparado de Aloe barbadensis mili. por vía inhalatoria - Migdalia Rodríguez Rivas; Ana I. Arias Gallardo; Francisco B. Pérez Villaverde; Marieni Hernández Paréis; Adalberto Olivera Hernández; Israel Guadarrama Suárez
No disponible